(untitled) (Global Journal of Management and Business Research, 2018)
This study aims to examining the impact of Human Resources Management Practices on organizational commitment of the employees of commercial Banks in Jordan. Human Resources Management Practices which were included in the study are: staffing, training and development, compensation, and performance appraisal, on the other hand, the Organizational commitment was measured by three dimensions: affective Commitment, normative commitment, and continuance commitment which was developed by Allen and Meyer (1990). The study population consists of all employees working in commercial banks in Jordan, samples of 425 employees were selected to represent the study population, and the researchers distributed the questionnaires to the study sample. To achieve the study objective, and to test hypotheses, the statistical program of social studies (SPSS) was used. The study findings showed that human resources management practices (staffing, training and development, compensation, and performance appraisal) had a significant and positive effect on the employees’ commitment of commercial Banks in Jordan. Based on the study results the researcher recommends managers and decision makers of commercial banks in Jordan to activate Human resources practices more inside the banks, develop the mechanisms and procedures to demonstrate them, and follow effective styles to execute them and show more interest in the process of employeesâ€™ empowerment.